1971
DOI: 10.1128/jvi.8.6.842-849.1971
|View full text |Cite
|
Sign up to set email alerts
|

Paracrystal Formation in Cell Cultures Infected with Adenovirus Type 2

Abstract: Large rod-shaped structures corresponding to paracrystals were seen in the nucleus, cytoplasm, or both of adenovirus type 2 (Ad2)-infected cells by immunofluorescence staining with antibody prepared against purified Ad2. In exception to this, Ad2-induced crystals did not stain with either hexon or fiber antibody. The crystalline structures were first observed in Ad2-infected Vero cells at 28 hr with a maximum number at 70 hr postinoculation. The kinetics of paracrystalline formation closely paralleled the expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1972
1972
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…At first, there was no uniform opinion on what component of the viral proteins formed the paracrystals. Some researchers thought that they represented an accumulation of capsid proteins synthesized in surplus (superfluous capsid subunits) [40][41][42][43]; others specified that they were formed from the filiform (fiber) protein [44]; and a third group of researchers suggested that paracrystalpils of the basic core protein could appear in the nuclei or cytoplasm [45][46][47][48]. It was found that paracrystals appear after 24 h and do not grow larger, and the cell culture type does not influence their presence or size (V. Karabasheva and I. Dobrev, personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…At first, there was no uniform opinion on what component of the viral proteins formed the paracrystals. Some researchers thought that they represented an accumulation of capsid proteins synthesized in surplus (superfluous capsid subunits) [40][41][42][43]; others specified that they were formed from the filiform (fiber) protein [44]; and a third group of researchers suggested that paracrystalpils of the basic core protein could appear in the nuclei or cytoplasm [45][46][47][48]. It was found that paracrystals appear after 24 h and do not grow larger, and the cell culture type does not influence their presence or size (V. Karabasheva and I. Dobrev, personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…At late times (~24 hpi), virus particles and protein crystals formed by penton base and fiber start to appear [ 28 , 29 ] ( Figure 1 B). At 36 hpi, particle production reaches its maximum [ 30 ] ( Figure 1 G) and the cell morphology is extensively altered.…”
Section: Introductionmentioning
confidence: 99%